Optimalisasi Tindak Tutur Direktif Guru Terhadap Pembentukan Karakter Siswa dalam Proses Pembelajaran - Baiq Nahdiyyati; Zuhdiniati Zuhdiniati; Misnawati Misnawati; Baik Rahmi Aulia Az-Zahra; Rabiul Awal; Hary Murcahyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe the use of teachers' directive speech acts in students' character-building during the learning process. This research uses a qualitative approach with a case study method. Primary data was collected in the form of speech from teachers in the form of directive speech acts. Primary data sources were obtained through direct observation or observation in the field. Secondary data were collected by recording. The subjects in this study were 11 subject teachers. Secondary data sources were obtained through documentation and direct recording. Data analysis went through six steps, including data collection, data simplification, data presentation, data classification, data interpretation, and conclusion drawing. In this study, the interaction conditions observed include: when entering the classroom, when starting the lesson, during the lesson, when the teacher gives assignments to students when the teacher asks for assignments from students, when the teacher asks students to correct the assignments, when concluding the lesson, and when ending the lesson. The conclusion is that the most dominant directive speech acts used are invitations, orders, and requests. The characteristics formed include discipline, religion, respect, curiosity, enthusiasm, responsibility, independence, hard work, collaboration, caring, and honesty. Keywords: directive speech acts, character, learning.